Do constitutional principles affect self-realization of the youth? - Elena A. Pevtsova; Irina A. Umnova-Koniukhova; Irina A. Aleshkova (RUDN Journal of Law, 2022)
The influence of constitutional principles on youth consciousness is a fundamental issue. Combined, constitutional and moral principles underlie behavior of young people in the society. They are of great relevance in the process of civil society formation. This paper examines the features of self-actualization of youth in Russia. We conducted a sociological survey of more than 200 students of higher educational institutions, most of them participating in the activities of youth public organizations in various areas: sports, politics, ecology, patriotic education, charity, etc. The survey showed that those who actively realized their talents and abilities and sought to express themselves in science and society were motivated by the constitutional guidelines; they were well aware of the content of legal prescriptions that specify constitutional principles. Many of the young people perceive constitutional principles as guarantees of their legal possibilities that determine the basis for their interaction with other subjects of law. Moreover, it was found that legal and moral values formed in the mind of a young person provide understanding of the content of constitutional principles and affect the behavior of a young person in the process of self-actualization.